Divining Proportions in the Information Age. Issue 1 (20th June 2014) - Tallon, Andrew
Abstract : The process of reverse engineering proportional systems of historic buildings has long been fraught with problems. One cannot assume, without knowing the specific conditions of acquisition, that existing plans are accurate enough to sustain the scrutiny necessary to resolve differences among potential proportional schemes. Yet producing a new survey with conventional measurement instruments could take weeks, if not months, and only in the best of situations would it be possible to acquire data in the upper reaches of the building—information required to avoid arbitrary dimensional rectification. With the advent of high-speed and high-precision laser scanning, however, the situation has changed dramatically.